A Meta-Analysis on Sex Differences in Resting-State Vagal Activity in Children and Adolescents - Koenig, Julian; Rash, Joshua A.; Campbell, Tavis S.; Thayer, Julian F.; Kaess, Michael (Frontiers in Physiology, 2017)
Lower vagal activity is associated with psychopathology independent of age. Research suggests that alterations of vagal activity precede the development of psychopathology. The present review aimed to quantify sex differences in vagal activity in children and adolescents. Studies reporting on sex differences on measures of vagally-mediated heart rate variability derived from short-recordings under resting conditions in boys and girls were included. Drawing on data from more than 5000 children and adolescents, we provide evidence that healthy young girls display lower vagal activity and greater mean heart rate compared to boys, a finding that may have implications for risk associated with the development of internalizing psychopathology and somatic ill-health.